Assembly of platinum nanoparticles and single-atom bismuth for selective oxidation of glycerol. Issue 45 (11th November 2021) - Huang, Ning; Zhang, Zihao; Lu, Yubing; Tian, Jinshu; Jiang, Dong; Yue, Chenguang; Zhang, Pingbo; Jiang, Pingping; Leng, Yan
Abstract : An assembly of platinum nanoparticles and N-stabilized single-atom bismuth shows unexpected high activity and selectivity for selective oxidation of glycerol to dihydroxyacetone. Abstract : Selective oxidation of the secondary hydroxyl group of glycerol to dihydroxyacetone (DHA) is an extremely challenging yet important reaction. The main difficulty is that the three hydroxyl groups in glycerol are prone to randomly oxidize, resulting in an unsatisfactory DHA selectivity. We show here that an assembly of platinum nanoparticles (NPs, ∼2 nm) and N-stabilized single-atom bismuth (Bi), namely Pt/Bi@NC, shows a record-high DHA selectivity of ∼95.0% towards glycerol oxidation under optimized reaction conditions. Characterization and theoretical calculations confirm that single-atom Bi in the vicinity of Pt NPs provides a preferred site to chelate with the primary –OH of glycerol, and its secondary –OH is prone to bind to a surface Pt atom of a Pt NP with a shorter Pt–H bond length. This as-formed unique adsorption configuration of glycerol on the Pt–Bi dual site significantly facilitates the oxidation of the secondary –OH of glycerol, thus contributing to a record-high selectivity to DHA.